Itching as the onset of pain (part 2) - Kushnir, Valerii; Dmytrenko, Svitlana; Katilov, Oleksandr; Kushnir, Nataliia (Pain medicine, 2020)
Itching of the skin is a particularly unpleasant subjective sensation that causes the need to scratch. Physiological itching occurs in response to environmental irritants (friction, insect crawling, temperature changes, etc.) and disappears after elimination of the cause. Pathological itching is caused by changes in the skin or throughout the body and causes a strong need to get rid of itching by combing or any other method. Itching is a common symptom of local (dermatological) or general (systemic) disease. It can be limited (localized) or diffuse (generalized). One of the causes of itching is often noted endocrine diseases and metabolic disorders: hyper- and hypofunction of the thyroid gland, diabetes mellitus and hyperparathyroidism. In thyroid hyperfunction, generalized (inconstant and little-pronounced) itching of the skin is observed in the clinical picture only in 10 % of patients. It is accepted that itching of the skin in thyrotoxicosis syndrome is due to increased activity of kinin in combination with an increase in major metabolism and an increase in body and skin temperature (123). Itching caused by impaired bile secretion is characteristic of many diseases of the liver: primary biliary cirrhosis, sclerosing cholangitis, viral hepatitis caused by cholestasis medications and other causes of obstructive jaundice. It is in these cases that prurigo is usually generalized, but in some typical cases it is more pronounced on the feet and palms. With this pathology, itching is caused by obstruction of the biliary tract, however, and to this day, no close correlation has been found between serum bilirubin and the severity of itching. If it was previously thought that itching in pathology of the peripheral or central nervous system, such as multiple sclerosis, neuropathy, compression or irritation of nerves (e.g., paraesthetic dorsalgia, brachioradial itching) is also a significant symptom, then modern studies prove that in more cases, itching is not characteristic of most pathologies of the nervous system, so after a detailed anamnesis, examination and initial research, the patient should be referred to a related specialist, except in cases of about obvious postherpetic neuropathy, painless paresthesia, or brachioradial itching, which can often be guided in the provision of primary care. Instead, there are some psychological conditions and a number of psychiatric illnesses (obsessive-compulsive disorders, depression, and parasite illusions) that are most commonly diagnosed with the exclusion method. Neurotic squabbles are scattered on the body of the excorii, covered with scales that may occur in any area of the body that the patient may reach, but are often limited by limbs.